155k views
3 votes
Integration using part formula

\int\limits {x^nlogx} \, dx

User Junique
by
4.8k points

1 Answer

2 votes

Answer:

Integration of I=
\int {x^(n)logx \, dx=
[(logx)/(n+1) x^((n+1))]-[(1)/((n+1)^(2))x^((n+1))]

Explanation:

Given integral is I=
\int {x^(n)logx \, dx

Take logx=t


x=e^(t)


x^(n)=e^(nt)


(1)/(x) dx=dt


dx=xdt


dx=e^(t)dt

I=
\int (e^(nt))(t)(e^(t))\, dt

I=
\int (e^((n+1)t))(t)\, dt

Using integration by part,


I= (t)\int [e^((n+1)t)]\, dt-\int[(d)/(dt){t}*\int (e^((n+1)t))]\\\\I= (t) [(1)/(n+1)e^((n+1)t)]-\int[1*(1)/(n+1)e^((n+1)t)]\,dt\\\\I=[(t)/(n+1)e^((n+1)t)]-[(1)/((n+1)^(2))e^((n+1)t)]

Writing in terms of x

I=
[(t)/(n+1)e^((n+1)t)]-[(1)/((n+1)^(2))e^((n+1)t)]

I=
[(logx)/(n+1)e^((n+1)logx)]-[(1)/((n+1)^(2))e^((n+1)logx)]

I=
[(logx)/(n+1)e^{logx^((n+1))}]-[(1)/((n+1)^(2))e^{logx^((n+1))}]

I=
[(logx)/(n+1) x^((n+1))]-[(1)/((n+1)^(2))x^((n+1))]

Thus,

Integration of I=
\int {x^(n)logx \, dx=
[(logx)/(n+1) x^((n+1))]-[(1)/((n+1)^(2))x^((n+1))]

User SharmaPattar
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.